Toward effective nature conservation on farmland: making farmers matter. Issue 1 (5th November 2012) - de Snoo, Geert R.; Herzon, Irina; Staats, Henk; Burton, Rob J.F.; Schindler, Stefan; van Dijk, Jerry; Lokhorst, Anne Marike; Bullock, James M.; Lobley, Matt; Wrbka, Thomas; Schwarz, Gerald; Musters, C.J.M.
Abstract Until now the main instrument to counteract the loss of biodiversity and landscape quality in the European countryside has been agri‐environment schemes (AES), which offer short‐term payments for performing prescribed environmental management behaviors. In our opinion this approach is, in its current set‐up, not a sustainable way of enhancing biodiversity and landscape quality. Here we will argue that conservation in agricultural areas is also a social challenge. To change farmers' behaviors toward more sustainable conservation of farmland biodiversity, instruments should aim to influence individual farmer's motivation and behavior. We should aim to place farmland biodiversity "in the hands and minds of farmers."